Construction of nitrification model with nitrifying coal ash in aerobic treatment of high strength wastewater - Liu, Fang; Zhao, Xin; Pan, Yujin; Hu, Xiaomin (Journal of Environmental Engineering and Landscape Management, 2022)
Nitrifying carriers can provide good settle ability and stable removal efficiency for nitrogen. Models for ammonia removal rate for nitrifying carriers will improve its engineering application. This study was conducted in nitrifying coal ash system with Monod model. Results indicated the maximum NH4+-N removal rate and half-saturation constant of NH4+-N in Monod model were 110.48 mg/L and 59.19 mg/L, respectively. Introduction of the correction coefficients, including pH, temperature and dissolved oxygen (DO) concentration, decreased the average gap between experiment data and simulated data from 6.48 to 2.74 mg N/(L·h). And improved accuracy of the Monod model by 5.11%. The differences between experiment and simulated NH4+-N removal rate ranged from 0.08 mg N/(L·h) to 8.34 mg N/(L·h) when the influent concentration of NH4+-N increased from 443.18 to 1121.29 mg N/L and without organic. Only 0.08% inconsistency between experiment and simulated data occurred in treating wastewater with high-strength ammonia. However, NH4+-N removal rate of the nitrifying coal ash was inhibited about 40% when influent with averaged 173.19 mg COD/L and 37.20 mg N/L, therefore, other factors, the content of nitrifying bacteria for example, need to be introduced into the Monod model when treating organic wastewater.